2018
DOI: 10.1001/jamaoncol.2018.2961
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Treatment and Survival in Patients With Myeloma

Abstract: Based on PFS and OS results of this NMA, lenalidomide maintenance appears to be the best treatment option, by synthesizing the available evidence of novel agent-based maintenance in the past 20 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 56 publications
1
40
0
1
Order By: Relevance
“…The hazard ratio (HR) for progression or death was 0.72, which is similar to data from the Nordic/ German group on bortezomib in this setting [3]. In light of a recent meta-analysis investigating different maintenance regimens, lenalidomide still shows substantially better survival data and should remain standard of care [4].…”
Section: Newly Diagnosed Transplant Eligiblesupporting
confidence: 72%
“…The hazard ratio (HR) for progression or death was 0.72, which is similar to data from the Nordic/ German group on bortezomib in this setting [3]. In light of a recent meta-analysis investigating different maintenance regimens, lenalidomide still shows substantially better survival data and should remain standard of care [4].…”
Section: Newly Diagnosed Transplant Eligiblesupporting
confidence: 72%
“…2 In particular, increasing the adoption of lenalidomide earlier in the myeloma treatment paradigm as maintenance therapy post high-dose melphalan and autologous stem cell transplantation (ASCT), or as a first-line therapy for elderly patients, has resulted in an increasing need for effective treatments for lenalidomide-refractory RRMM. 3,4 Efficacy results from phase 3 studies of novel combination therapies in lenalidomide-refractory patients remain unsatisfactory, and recent studies of lenalidomide-based combination therapies in RRMM exclude lenalidomide-refractory patients. [5][6][7][8][9][10] Daratumumab is a human immunoglobulin Gk (IgGk) monoclonal antibody targeting CD38 with a direct on-tumor [11][12][13][14] and immunomodulatory mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Using primary samples, Chaidos et al [77] showed that the malignant counterparts of plasmablasts and pre-plasma cells could reconstruct MM in immunodeficient mice upon transplantation. From these observations, it can be speculated that IMiDs preferentially target MM stem cells, providing a molecular basis for the clinical finding that post-transplantation maintenance with lenalidomide significantly prolonged the survival of MM patients [85][86][87][88][89][90]. However, much less is known about the mechanism underlying the preferential effects of IMiDs on MM stem cells.…”
Section: Clonal Composition Affects Drug Sensitivitymentioning
confidence: 99%